Utility of multipurpose trees as black pepper (Piper nigrum L.) standards in the humid tropics of Kerala - Kunhamu, T.K.; Kumar, B. Mohan; Jamaludheen, V. (Indian Journal of Agroforestry, 2020)
A field study was carried out at Thiruvazhamkunnu, Kerala from June 1988 to August 2005 to evaluate the performance of six fast growing multipurpose tree species (MPTs) viz. Artocarpus heterophyllus, Macaranga peltata,Â Ailanthus triphysa, Grevillia robusta, Acacia auriculiformis and Casuarina equisetifolia as support for black pepper. Results pertaining to 10 years (1995-2005) peak pepper production are discussed in this paper. Significant variation in pepper yield among the support trees was observed. At the end of 17 years of stand establishment, the maximum dry pepper yield was from A. auriculiformis standards (2.56 Mg ha-1) followed by A. heterophyllus (1.91 Mg ha-1), AilanthusÂ triphysa (0.93 Mg ha-1) and Macaranga peltata (0.83 Mg ha-1). Among the support trees A. auriculiformis, M. peltata and A. heterophyllus showed better growth. Lopped biomass yield also varied considerably among the support trees with highest yield from Artocarpus heterophyllus (1.28 Mg ha-1) followed by Acacia auriculiformis and M. peltata which were at par (1.08 Mg ha-1). While M. peltata and A. heterophyllus were the toppers in annual litter production (4.65 and 4.55 Mg ha-1 yr-1 respectively), A. triphysa recorded the lowest value (2.22 Mg ha-1 yr-1). Results in general, suggest the suitability of A. auriculiformis and A. heterophyllus for block cultivation of black pepper. In addition to the biophysical advantage of these tree species in improving the site productivity, higher longevity and timber revenue at final rotation are other potential advantages of these MPTs over conventional pepper support trees such as Erithrina indica.